A educação está no ar: a comunicação pública no Programa Jornal da Educação da Rádio Universitária FM - Pimentel, Cristiane Maria Sales (2017)
This research analyzes the "Jornal da Educação" (Education News), news program of the University FM Radio Station 107,9 MHZ. The radio is part of Research and Culture Foundation of Ceará, in terms of legal order and financial resources, and Ceará´s Federal University, in terms of facilities, personnel, management and programming. This research analyzes how and under which aspects the theme of Brazilian Education, with its initiatives and public policies, is approached by this news program of the University FM Radio, that went on air for over a decade (2004 - 2016). Therefore, nineteen scripts and nineteen audio recordings are studied, referring to live broadcasts from June 2015. The month was chosen because of its topic, period when the production team had as a goal prepare a special series of programs that discussed the first year of Brazil´s National Education Plan, validity 2014-2024. It also is verified how does the Public Communitation is developed at the program, since the beginning of selection and writing of the stories until the live broadcasts. Throughout this master´s thesis, a historical review is made about Educational Radio and Radiojournalism in Brazil, observing this trajectory enlightened by the concept of Public Communication. Making a brief report about the legal and social path of the ideals of right to information and freedom of speech, the work relates the pratice of citizenship in Western democracies to the expansion of communication possibilities. The public sphere of Habermas and its criticism is presented as theoretical inspiration, as well as the attempt of delineate the concept of public communication proposed by the French researcher Pierre Zémor and the Brazilian authors Jorge Duarte, Elizabeth Brandão, Eugênio Bucci, Mariângela Furlan Haswani, Regina Escudeiro and Heloísa Matos; currently the main exponents of this field. Understanding that the educative communication integrates one of the branches of public communication, this work analyzes the pioneering of radio in the practice of this area of communications in Brazil.